2012
DOI: 10.1103/physrevc.86.044322
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies in the description of pairing effects in nuclear level densities

Abstract: Pairing correlations have a strong influence on nuclear level densities. Empirical descriptions and theoretical models have been developed to take these effects into account. The present article discusses cases, where descriptions of nuclear level densities are inconsistent or in conflict with the present understanding of nuclear properties. Phenomenological approaches consider a back-shift parameter. However, the absolute magnitude of the back-shift, which actually corresponds to the pairing condensation ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
(66 reference statements)
1
32
1
Order By: Relevance
“…[63]. This is in conflict with the fact that pairing correlations are only stable, if they increase the nuclear binding.…”
Section: B Nuclear Level Densitiescontrasting
confidence: 44%
See 1 more Smart Citation
“…[63]. This is in conflict with the fact that pairing correlations are only stable, if they increase the nuclear binding.…”
Section: B Nuclear Level Densitiescontrasting
confidence: 44%
“…There exist several descriptions that differ substantially, in particular in their low-energy characteristics. A recent analysis revealed that many of these descriptions are not consistent with our present understanding of nuclear properties [63]. The result can be summarized as follows:…”
Section: B Nuclear Level Densitiesmentioning
confidence: 53%
“…In order to include the effects of pairing correlations on the nuclear level density in a realistic way, the recommended energy shift of the Fermi-gas part of the Gilbert-Cameron composite formula [11] is increased by 2 MeV. Consequently, in our composite formula the transition from the constanttemperature to the Fermi-gas regime occurs at energies of about 8-9 MeV which are higher than the transition energies of the broadly used Gilbert-Cameron formula [12]. For fragment energies larger than the transition energy, the level densities of the fragments follow the Fermi-gas description.…”
Section: -P4 Fission 2013mentioning
confidence: 99%
“…We require that the most probable values of the χ k 's at any CN excitation energy E * maximize the entropy S. As regards the choice of the level density (the logarithm of which yields S), it has been suggested [63] that a composite Gilbert-Cameron (CGC) formula, with a larger energy shift and a multiplicative enhancement in the Fermi gas regime, encapsulates qualitatively the influence of shell effects, collective excitations and pairing correlations on the level density. In lieu of specific information on the magnitude of these modifications for 150 Sm, we employ both the back-shifted Fermi gas (BSFG) and the constant temperature (CT) formulas, with 150 Sm parameters (appropriate to E * < 10 MeV) taken from Table II in Ref.…”
mentioning
confidence: 99%